Utilization of the Drama Script My Father Goes Home by Usmar Ismail as Teaching Material for Indonesian Language Learning in High Schools - Lusiana, Khoirun Nisa (UIR Press, 2024)
This research is important for analyzing the content of drama, the linguistic rules of drama and its suitability as learning teaching material. This study aims to explain the content, linguistic rules and suitability as teaching material. This type of research is qualitative descriptive research using a structural approach in analyzing data. The data and data sources in this research come from dialogues contained in drama scripts, drama theory books, and articles that are reference sources. Data collection using observation techniques, interviews and note taking. Then, to analyze the data using a flow mode technique consisting of data reduction, data collection and collection. The results obtained include: First, analysis of the content of the drama script which includes the building blocks of drama. The building blocks of drama consist of intrinsic elements and extrinsic elements. The intrinsic elements of this drama include theme, characters and characterization, plot, setting, point of view, language style, and message. Meanwhile, these extrinsic elements include the author's background, cultural conditions and the values contained in the drama script. Second, the linguistic rules of drama which include 4 categories, namely using adverbs that express time sequence, using verbs that express events, using verbs that express something that is thought or felt and using adjectives that describe characters, places and atmosphere. Third, the suitability of the drama script is assessed from 3 aspects, namely language, psychology and cultural background. The results of this research indicate that this drama script is suitable for use as teaching material and reference for educators in learning activities at school